IONESCO, JOYCE AND SHAKESPEARE IN THE CINEMA OF MANOEL DE OLIVEIRA - Santos, Kedrini Domingos dos [UNESP] (Univ Fed Goias, Campus Catalao, 2019)
Literature and cinema constitute themselves a distinct semiotic system, an aspect that evidences the complexity of the relationship between these arts. The literature presents themes and narrative structures that can inspire cinematographic work. Both arts can provoke emotions and feelings through their images: while literature is associated with imagination, cinema puts the image before the spectator. Considering the cinema of the Portuguese filmmaker Manoel de Oliveira, and aware of the dialogue he maintains with other arts, especially with literature, we will seek to observe, from the film Je rentre a la Maison, the intertext of the film with three great works: The theater pieces: Ionesco's Le roi se meurt and Shakespeare's The Tempest, and James Joyce's novel Ulysses. We will seek to understand how these literary works are part of the Oliverira's film universe, becoming a fundamental element for the construction of meaning.
Keywords: Literature; Movies; Manoel de Oliveira; Intertextuality